KEPUASAN PASIEN SEBAGAI VARIABEL INTERVENING PADA PENGARUH FASILITAS DAN KUALITAS PELAYANAN TERHADAP LOYALITAS - Ika Lisdiana; Indra Prasetyo; C. Sri Hartati (CV. ALIM'SPUBLISHING, 2023)
The purpose of this study was to describe service quality and patient satisfaction and loyalty at RSIA Fatma Bojonegoro, to determine and analyze the effect of service quality on patient satisfaction, the influence of service quality directly on patient loyalty, the effect of patient satisfaction on patient loyalty, and the influence of service quality indirectly. on patient loyalty with patient satisfaction as an intervening variable. This type of research is explanatory using a quantitative approach. The population of 700 patients at RSIA Fatma Bojonegoro in November 2021 with a sample of 88 respondents. The sampling technique used was quota sampling. The data collection method used in this study is a questionnaire and documentation by analyzing it using path analysis, especially Partial Least Square (PLS). Based on the results of the analysis, it can be concluded that service quality and patient satisfaction and loyalty at RSIA Fatma Bojonegoro are in good category, service quality has a significant influence on patient satisfaction, service quality has a direct significant effect on patient loyalty, patient satisfaction has a significant influence on patient satisfaction. patient loyalty, service quality has a significant indirect effect on patient loyalty with patient satisfaction as an intervening variable.